Glokalisasi UMKM melalui BUMN: Studi Kasus PT Pos Indonesia sebagai Media Diplomasi Ekonomi Indonesia - Ageu Lagena; Rizki Ananda Ramadhan; Gilang Nur Alam (Jurnal Ilmu Sosial dan Ilmu Politik (JISIP), 2026)
Micro, Small, and Medium Enterprises make a significant contribution to the national economy; however, their competitiveness at the global level remains relatively limited due to various structural constraints, including restricted access to capital, low digital literacy, and logistical barriers. This study aims to analyze how the concept of glocalization can be applied as a strategy to encourage micro, small, and medium enterprises to enter the global market, positioning State-Owned Enterprises, particularly PT Pos Indonesia as the primary facilitator within an economic diplomacy framework. The study employs a qualitative approach with a case study design, in which data were gathered through semi-structured in-depth interviews with internal actors at PT Pos Indonesia who have access to policies and practices related to the empowerment of micro, small, and medium enterprises, and were subsequently analyzed interactively. The findings reveal that PT Pos Indonesia's national and international logistics network, digital infrastructure support, and cross-institutional collaboration enable it to function as an integrated solution, particularly through export facilitation initiatives. The novelty of this research lies in its analytical framework, which integrates the concept of glocalization with an economic diplomacy approach through the role of State-Owned Enterprises, which is a perspective that has received limited scholarly attention in the existing literature. This study concludes that optimizing the role of PT Pos Indonesia has the potential to strengthen the global competitiveness of micro, small, and medium enterprises while simultaneously supporting the advancement of Indonesia's economic diplomacy on the international stage.Usaha Mikro, Kecil, dan Menengah memiliki kontribusi yang signifikan terhadap perekonomian nasional, namun daya saing mereka di tingkat global masih relatif terbatas akibat berbagai kendala struktural, antara lain keterbatasan akses permodalan, rendahnya literasi digital, serta hambatan logistik. Penelitian ini bertujuan menganalisis bagaimana konsep glokalisasi dapat diterapkan sebagai strategi dalam mendorong usaha mikro, kecil, dan menengah memasuki pasar global, dengan menempatkan Badan Usaha Milik Negara, khususnya PT Pos Indonesia, sebagai fasilitator utama dalam kerangka diplomasi ekonomi. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus, di mana data diperoleh melalui wawancara mendalam semi-terstruktur dengan aktor internal PT Pos Indonesia yang memiliki akses terhadap kebijakan dan praktik pemberdayaan usaha mikro, kecil, dan menengah, kemudian dianalisis secara interaktif. Hasil penelitian menunjukkan bahwa jaringan logistik nasional dan internasional, dukungan infrastruktur digital, serta kolaborasi lintas lembaga memungkinkan PT Pos Indonesia berfungsi sebagai solusi terpadu, terutama melalui inisiatif fasilitasi ekspor. Kebaruan penelitian ini terletak pada kerangka analisis yang memadukan konsep glokalisasi dengan pendekatan diplomasi ekonomi melalui peran Badan Usaha Milik Negara, sebuah perspektif yang belum banyak dikaji dalam literatur sebelumnya. Penelitian ini menyimpulkan bahwa optimalisasi peran PT Pos Indonesia berpotensi memperkuat daya saing global usaha mikro, kecil, dan menengah sekaligus mendukung penguatan diplomasi ekonomi Indonesia di panggung internasional.